Pengembangan lembar kerja peserta didik dengan menggunakan model discovery learning berbantuan quizizz pada materi bangun ruang sisi datar - Rizkiyah Rohmah; Sugandi, Asep Ikin; Rosyana, Tina (IKIP Siliwangi, 2023)
This research aims to develop LKPD using a discovery learning model assisted by Quizizz that is feasible and practical. The method used in this research is the Research and Development (R&D) method with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. This research was carried out at SMP Negeri 3 Ngamprah, with the research subjects being 30 class VIII students. Data collection techniques use expert validation questionnaires and student response questionnaires. Data processing was carried out using Microsoft Excel. The research results show that the LKPD development process is by the ADDIE stages, the feasibility of LKPD using a model using the discovery learning model assisted by Quizizz according to experts and practitioners is in the very valid category and terms of practicality it is in the practical category.